2015
DOI: 10.1002/psp.1955
|View full text |Cite
|
Sign up to set email alerts
|

Parents' Migration and Children's Subjective Well‐being and Health: Evidence from Rural China

Abstract: This study examines differences in children's subjective well‐being and health across the full range of family structures that have emerged in China's rural areas because of parental labour migration. It uses original cross‐sectional survey data collected in 2010 in Anhui and Jiangxi provinces from children aged 8–17 years, as well as from their teachers and guardians (n = 992). The results indicate no significant difference between ‘left‐behind’ children and other children for satisfaction with life events. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…The main consensus is that the majority of rural migrants in cities lead second-class lives without much access to urban benefits. Studies have also suggested negative health and wellbeing consequences of rural-urban migration to migrants themselves (Song and Sun, 2015), and to the elderly and children left behind in the rural areas (Ao, Jiang, and Zhao, 2016;Li, Liu, and Zang, 2015;Xu and Xie, 2015;Murphy, Zhou, and Tao, 2015;Logan, 2011;De Brauw and Mu, 2011;Lee, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…The main consensus is that the majority of rural migrants in cities lead second-class lives without much access to urban benefits. Studies have also suggested negative health and wellbeing consequences of rural-urban migration to migrants themselves (Song and Sun, 2015), and to the elderly and children left behind in the rural areas (Ao, Jiang, and Zhao, 2016;Li, Liu, and Zang, 2015;Xu and Xie, 2015;Murphy, Zhou, and Tao, 2015;Logan, 2011;De Brauw and Mu, 2011;Lee, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…LBC who were brought up by grandparents, with a low frequency of communication with parents, tend to have poorer subjective well-being than children from intact families [10,11]. Many of these children suffer mental health problems such as poor confidence, depression, anxiety, loneliness and behavioral problems [11,12].…”
Section: Introductionmentioning
confidence: 98%
“…Many of these children suffer mental health problems such as poor confidence, depression, anxiety, loneliness and behavioral problems [11,12]. Boys showed more interpersonal problems such as misbehavior, reduced social interest and disobedience, and girls showed more negative self-esteem [13].…”
Section: Introductionmentioning
confidence: 98%
“…There are many studies that examine the discrimination against rural migrants and their inferior social and labor market positions [29,30]. Studies have also suggested negative health well-being consequences from rural-to-urban migration for migrants themselves [31], and to the elderly and children left behind in the rural areas [32,33]. The decision and determinants of rural-to-urban migration also concern many scholars [34,35].…”
Section: Introductionmentioning
confidence: 99%